DeMI interface tool for profit estimation and waste conversion technology recommendations in enhancing municipal solid waste management - Ali, R.A.; Nik Ibrahim, N.N.L.; Ghani, W.A.W.A.K.; Sani, N.S.; Lam, H.L. (Springer Science and Business Media LLC, 2024)
The DeMI Interface tool represents an innovative graphical user interface tool rooted in the Decision-Making Integration (DeMI) framework, offering decision makers a holistic approach within Process System Engineering (PSE). This state-of-the-art tool seamlessly combines process network synthesis and machine learning, using the Process Graph (P-graph) and the Waikato Environment for Knowledge Analysis (WEKA) software tools. By incorporating the P-graph methodology into the DeMI framework, the tool constructs a versatile superstructure that is designed to transform municipal solid waste (MSW) into valuable products. Leveraging the accelerated branch-and-bound algorithm, the P-graph efficiently generates optimal structures capable of accommodating diverse complexities, thus ensuring adaptability in synthesising process configurations. The true strength of the DeMI tool lies in its integration with WEKA, where it uses the feasible structures derived from the P-graph as a comprehensive database. By scrutinising correlations between variables within the process structure, DeMI provides invaluable insights into crucial aspects such as total waste weight, profit estimation, and the selection of appropriate waste conversion technologies. The M5P algorithm, adept at profit estimation, establishes correlations between MSW weight and profitability, while the J48 algorithm offers recommendations for suitable waste conversion technologies based on profit potential. With its intuitive and flexible interface, DeMI empowers decision makers to make informed decisions, thus enhancing decision-making in waste management and offering a promising model to address challenges in other industrial processes. In summary, DeMI makes a contribution to the advancement of PSE by offering a systematic approach to informed decision-making, underscoring its significance in optimising various industrial processes.